338 PREVALENCE AND PERSISTENCE OF HYPOVITAMINOSIS D AMONG ITALIAN PATIENTS WITH MYOCARDIAL INFARCTION. (15th December 2022) - Aleksova, Aneta; Gagno, Giulia; Pierri, Alessandro; Fluca, Alessandra Lucia; Janjusevic, Milijana; Derin, Agnese; Oriana Zhou, Xin Ning; Restivo, Luca; Hiche, Cristina; Stenner, Elisabetta; D'errico, Stefano; Zandonà, Lorenzo; et al.
Abstract: Background: Hypovitaminosis D is common in the Italian population and has a comparable effect to diabetes mellitus on survival after an acute myocardial infarction (AMI). We aimed to evaluate if the prevalence of hypovitaminosis D changed over time, considering also frequent lockdowns in the last years due to COVID-19 pandemic. Methods: According to the year of enrollment, we divided our cohort of 1042 patients hospitalized for AMI, into three groups (group 1 with 368 patients enrolled from 2014 till 2016, group 2 with 470 patients enrolled in the period from 2017 till 2019, and group 3 including 204 patients enrolled in the last three years, from 2020 till 2022) and evaluate whether the concentration of vitamin D changed in the last decade. Results: The median concentration of vitamin D in our cohort of patients with AMI was 18.2 (11.48-25.73) ng/ml). Throughout the three groups (2014-2016, 2017-2019, 2020-2022), the median plasma vitamin D showed a trend toward an increase (17.3 (10.33–24.2) ng/ml, 18.95 (11.6–26.73) ng/ml, and 19.05 (12.5–27.3) ng/ml respectively), which was significant between the group 1 vs 2 and 3 (p = 0.033 and p = 0.004, respectively), while between the group 2 and 3 did not. Despite the trend of increase, the percentage of patients with hypovitaminosis D in each group remained high (61.4%, 53.8% and 52.0% respectively). As expected, samples taken between May and September have significantly higher vitamin D values compared to ones taken from October to April for each group (the group 1: 21.80 (15.55–31.23) ng/ml vs 15.8 (9.22–23.98) ng/ml, p < 0.0001; the group 2: 22.05 (14.10–30.98) ng/ml vs 16.50 (11.03–23.90) ng/ml, p < 0.0001); the group 3: 20.00 (11.90–26.90) ng/ml vs 16.30 (9.75–22.30) ng/ml, p = 0.001). Conclusions: There has been a trend of increasing vitamin D values over the years, but hypovitaminosis D remains frequent. During the pandemic, vitamin D levels did not decrease due to frequent lockdowns, possibly due to media awareness that emphasized the significance of vitamin D administration against viral infection.